2016
DOI: 10.1016/j.jtbi.2016.07.034
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of vaccination and vector control on small dengue networks

Abstract: Dengue fever is a major public health issue affecting billions of people in over 100 countries across the globe. This challenge is growing as the invasive mosquito vectors, Aedes aegypti and Aedes albopictus, expand their distributions and increase their population sizes. Hence there is an increasing need to devise effective control methods that can contain dengue outbreaks. Here we construct an epidemiological model for virus transmission between vectors and hosts on a network of host populations distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…While it is difficult to parameterize a model of mosquito movement (though values between 4– migration between neighbouring villages are reported in [ 63 ]), the spatial ecology of A. gambiae will undoubtedly be crucial in determining the spread or containment of control efforts. The network model proposed here could be improved by including human movement [ 64 ] as a means to spread infection. Using the optimal control framework in such a model would require reformulating cost functions capable of capturing heterogeneous populations, which is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…While it is difficult to parameterize a model of mosquito movement (though values between 4– migration between neighbouring villages are reported in [ 63 ]), the spatial ecology of A. gambiae will undoubtedly be crucial in determining the spread or containment of control efforts. The network model proposed here could be improved by including human movement [ 64 ] as a means to spread infection. Using the optimal control framework in such a model would require reformulating cost functions capable of capturing heterogeneous populations, which is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…They are starting to show promising results. Predictive models have shown that weakly efficacious vaccination strategies against multiple virus serotype diversity can be counter-productive to disease control efforts [55], [60].…”
Section: Challenges With the Development Of Vaccinesmentioning
confidence: 99%
“…In particular, ordinary differential equations have been used to model the human mobility between two or more locations [9]. One approach is the continuous moving of the human population between places [10][11][12][13][14][15]. Other proposal is the residence time, which represents the proportion of time that human budget their residence across regions [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%